Infrastructure financing and bond markets development in sub-Saharan Africa - Mukoki, Paul Shepherd (My University, 2022)
This thesis explores how domestic public debt (bond) markets can be developed into viable mechanisms for closing the infrastructure funding gap existing in the sub-Saharan Africa (SSA) region. The infrastructure deficit in the SSA region is colossal and an impediment to its economic growth. To narrow the large deficits, Africa needs to bridge its infrastructure financing gap, estimated at US$62 billion annually until 2025. On the other hand, domestic public debt markets are seen as a potential funding source for filling this huge financing gap, but they are not considered well-developed. We first examined the relationship between bond markets development and the infrastructure gap in Sub-Saharan Africa. We employed the panel threshold regression (PTR) model on 40 countries covering 2003-2018 and documented a non-linear (single-triple) relationship between public debt market development and the infrastructure gap. We established that many of the fledgling government and corporate bond markets play a complementary role in the financing of infrastructure; and interestingly, with corporate public debt markets eliciting a greater reduction in the infrastructure financing gap than government public debt markets. We then used a cross-country survey approach on 8 SSA countries and nonparametric inferential statistics to investigate, first, the state of the public bond markets in SSA and, second, the ways by which their liquidity can be improved so that infrastructure investment can be enabled. The major conclusions from these survey results are: First, government yield curves do not provide a reliable benchmark for corporate bonds. Second, the government bond markets, which are expected to offer foundational mechanisms for establishing robust and effective yield curves, have remained underdeveloped. Commercial banks remain the predominant investorsin government bond markets, followed by nonbank financial institutions, and a few foreign investors, in that order. Third, except for South Africa, only 38% of the corporate bond markets in SSA are moderately developed; the rest are either developing (25%) or nascent (25%). Fourth, pension funds in many SSA countries have somewhat reformed to engage in infrastructure financing, though within statutory limits. Fifth, liquidity in government bond and corporate bond markets is relatively low in many countries, which in turn, limits infrastructure financing. Finally, we found that sophisticated financial instruments could facilitate infrastructure financing by deepening and fostering liquidity in domestic public debt markets. These instruments include infrastructure project bonds, diaspora bonds, green bonds, and vi securitised debt assets. An important part of this initiative involves increasing the sale of stateowned enterprise bonds and municipal bonds backed by guarantees from the government. The overall results show that the public debt markets in many of the surveyed SSA countries are underdeveloped and cannot significantly plug the infrastructure financing gap in the region unless substantial capital (especially public debt) markets growth and/or development are embarked upon.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Finance to the Graduate School of Business Administration of the University of the Witwatersrand
Keywords: Public debt markets; Infrastructure deficit; Market liquidity; UCTD; SDG-8: Decent work and economic growth; SDG-10: Reduced inequalities